Grafting Cucumber Onto Pumpkin Induced Early Stomatal Closure by Increasing ABA Sensitivity Under Salinity Conditions - Niu, Mengliang; Sun, Shitao; Nawaz, Muhammad Azher; Sun, Jingyu; Cao, Haishun; Lu, Junyang; Huang, Yuan; Bie, Zhilong (Frontiers in Plant Science, 2019)
During early periods of salt stress, reduced stomatal opening can prevent water loss and wilting. Abscisic acid (ABA) signal plays an important role in this process. Here, we show that cucumber grafted onto pumpkin exhibits rapid stomatal closure, which helps plants to adapt to osmotic stress caused by salinity. Increased ABA contents in the roots, xylem sap, and leaves were evaluated in two grafting combinations (self-grafted cucumber and cucumber grafted onto pumpkin rootstock). The expression levels of ABA biosynthetic or signaling related genes NCED2 (9-cis-epoxycarotenoid dioxygenase gene 2), ABCG22 (ATP-binding cassette transporter genes 22), PP2C (type-2C protein phosphatases), and SnRK2.1 (sucrose non-fermenting 1-related protein kinases 2) were investigated. Results showed that a root-sourced ABA signal led to decreased stomatal opening and transpiration in the plants grafted onto pumpkin. Furthermore, plants grafted onto pumpkin had increased sensitivity to ABA, compared with self-grafted cucumbers. The inhibition of ABA biosynthesis with fluridon in roots increased the transpiration rate (Tr) and stomatal conductance (Gs) in the leaves. Our study demonstrated that the roots of pumpkin increases the sensitivity of the scion to ABA delivered from the roots to the shoots, and enhances osmotic tolerance under NaCl stress. Such a mechanism can be greatly exploited to benefit vegetable production particularly in semiarid saline regions.